Bridging the science policy gap through an online knowledge sharing platform - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Recording of webinar to introduce the Climate and Agriculture Network for Africa (CANA). Speakers: James Kinyangi, Regional Program Leader CCAFS East Africa Victor A. Orindi National Drought Management Authority - Kenya Vivian Atakos, Communication Specialist CCAFS East Africa Grace Katiku, Pamoja Media